BeeHive Co-Working with Green Architecture Approach - Saiful Bahri Pane; Cut Nuraini; Fariz Harindra Syam (International Forum of Researchers and Lecturers, 2022)
Mainstream work activities that are generally carried out in rigid office spaces sometimes cause boredom for workers. Variations in ways and places of working need to be accommodated to avoid boredom. BeeHive Co-Working was built with the aim of providing a new place to work and socialize which is expected to provide enthusiasm in carrying out work activities. The design method applied is through a process that begins with the problem of how to create a flexible, relaxed, and unpressured work environment. The idea of Co-Working design is proposed to answer the initial problem. Green Architecture theme is proposed as the main theme of BeeHive Co-Working design. The concept of Green Architecture used in this design takes the main focus as a building that is energy efficient, minimizes expenses and increases the added value of the building. The position of the building in green architecture is related to (1) being able to adapt to solar circulation and wind direction, (2) extending from east to west, blocking solar radiation on transparent walls, (3) reducing heat transmission from massive walls exposed to direct solar radiation. The design of BeeHive Co-Working, which applies the concept of Green Architecture, is realized in the form of a modern design transformed from a rectangular mass form with a front view that uses an additional honeycomb-shaped facade. BeeHive Co-Working facilities that support the function of casual work are accommodated by the provision of furniture designed for the convenience of working while relaxing. The commercial function is supported by the provision of café shop facilities. This design is expected to be a place for workers to restore energy from the fatigue of busy work activities.